Graeme Goldsworthy omnibus - Goldsworthy, Graeme Lister, 1934- (Carlisle, UK Paternoster, 2000)
Contents : Gospel and kingdom (1981); The Gospel in Revelation (1984), which see also; Gospel and wisdom (1987), which see also.
Keywords: Bible -- theology